Pengaruh Overconfidence Manajer Dan Capital Intensity Terhadap Penghindaran Pajak Yang Dimoderasi Oleh Kualitas Audit - Elia Rossa (Universitas Pamulang, 2022)
This study aims to examine the moderating role of audit quality on the effect of manager overconfidence and capital intensity on tax avoidance. The sample samples selected using the purposive sampling method consist of Indonesia public manufacturing companies for the periode 2015-2019. It employs SEM-PLS to test the hypotheses. The results show that manager overconfidence has a negative and significant effect on tax avoidance, capital intensity has a positive and significant effect on tax avoidance. Audit quality does not moderate the effect of manager overconfidence and capital intensity on tax avoidance. The study confirms that managers overconfidence reduces tax avoidance practices